APPLIED BACCALAUREATE AS THE MAIN MECHANISM OF THE HIGHER EDUCATION PROFESSIONALISATION - G F Tkach (RUDN Journal of Informatization in Education, 2016)
The article reviews the main conceptual and legal provisions and organizational activities carried out in the education system of the Russian Federation in order to introduce the new educational programs of applied bachelor degree. The problem of effective professionalization of higher education is extremely relevant due to the serious problems that Russian higher education currently faces. One of such problems is the lack of practical suitability of Bachelor graduates to the conditions and requirements of the actual labor. Responding to this problem, in Russia, as in most developed countries, there is a way to improve the professionalisation in the first stage of higher education - to divide the educational program of Bachelor into “academic” or “general” and “applied” or “professional”. The same issue is relevant to the different qualifications and assigns.The review of the experience of educational reforms in the leading European countries, where during the last 15-20 years some large-scale reforms with a view to the professionalization of higher education were carried out. It is important, that the essence of these reforms underlined the general problem of rapid modernization of vocational training structure and content of educational programs in accordance with labor market demands and socially important requests of individual regions and the country in common. The analysis of the success of the reforms carried out in different countries, shows that it is common for all to establish a close relationship of employers and educational institutions at a sufficiently broad autonomy to the last, in cooperation with the state regulation of educational activities.This organic combination of theoretical and practical components of the secondary and higher vocational education programs of applied bachelor degree programs is to become the basis of the formation process of a new professional category, mostly demanded by the labor market.